Perbandingan Kinerja Peta Kendali Exponentially Weighted Moving Average dan Peta Kendali Double Exponentially Weighted Moving Average dalam Pengendalian Kualitas Produksi Butsudan di PT. Maruki International Indonesia - Sonya, Sonya; Herdiani, Erna Tri; Tinungki, Georgina Maria (ESTIMASI: Journal of Statistics and Its Application, 2025)
Quality control is an effort in the production process to maintain product quality and minimize the occurrence of defects. One of the quality control tools is a control chart. An exponentially weighted moving average (EWMA) control chart is used to detect small shifts in the process mean. The result of the development of the EWMA control chart is the double exponentially weighted moving average (DEWMA) control chart, which increases the exponential smoothing process, where the control chart is considered more sensitive in detecting small shifts in the process mean. This study aims to obtain a comparison of the performance of the EWMA and DEWMA control charts in controlling the quality of butsudan production at PT. Maruki International Indonesia. The results obtained show that the DEWMA control chart has better performance in detecting small shifts compared to the EWMA control chart based on the smallest ARL value, at λ=0.1 the DEWMA control chart has an ARL value 1.1363 which is smaller than the ARL of EWMA control chart is 1.2268.